Advances in immunological sorting of X and Y chromosome-bearing sperm: from proteome to sex-specific proteins - Bai, Linfeng; Zhao, Yue; Zhou, Yang; Song, Yongli; Xiao, Hao; Zhao, Gaoping; Wang, Zhigang; Li, Xihe (Frontiers in Veterinary Science, 2025)
Sex determination is the developmental assignment that results from genetic factors. The sexual characters were the specific manifestations of male and female individuals under stimulation of sexual hormonal production. The fusion of an oocyte with an X chromosome-bearing sperm will lead to a female (XX), while fusion with a Y chromosome-bearing sperm will develop into a male (XY) in mammals. Sexing technology has been developed to fertilize eggs with sorted sperm, producing offspring of the desired sex. Sperm sorting enables the sex pre-determination of offspring via in vitro fertilization (IVF) or artificial insemination (AI) in domestic animals. Flow cytometric sorting of X and Y sperm is widely considered the most applied method for sperm sorting and has been commercially applied in cattle. However, a non-invasive, immunological method for screening X and Y sperm is considered to be a feasible approach. This review summarizes the current knowledge and techniques of sperm immunological sorting, including the preparation of antibodies, application of immunomodulators, and immunoisolation. Additionally, we focus on identifying sex-specifically expressed proteins in X and Y sperm through proteomic analysis, and verifying the sex-specific proteins using experimental techniques. Furthermore, several housekeeping proteins as loading control were discussed in immunoblotting of sperm proteins. Immunological sorting of X and Y sperm could provide a convenient, cost-effective, and highly efficient technique that can improve economic benefits and achieve an advanced level of sexing technology. This review provides insight into immunological sorting of sperm and the pre-determination of sex in farm animals.